A Collaborative Accountability in Mosque Governance: Integrating the Value of Ta’awun and Agency Theory at the Muhammad Cheng Ho Mosque - Maharani, Maharani; Sugianto, Sugianto; Kahar, Abdul; Usman, Ernawaty (Dinasti Publisher, 2026)
This study aims to reveal a collaborative accountability model in the governance of the Muhammad Cheng Ho Mosque through the integration of agency theory and Ta’awun values as the basis for ethical accountability. A ideographic configurative case study approach was used to explore patterns of relationships and accountability practices between mosque administrators, congregations, and companies as key actors in the religious non-profit accountability system. Data were obtained through in-depth interviews and documentation, then analyzed thematically to reveal the configuration of meanings that shaped accountability practices. The results show that accountability is carried out in two main dimensions: the formal dimension, through open financial recording and reporting to congregations and corporate partners; and the social-spiritual dimension, through the internalization of the values of trust, honesty, and the spirit of Ta’awun in mosque activities. The integration of these two dimensions gives rise to a collaborative accountability model that not only strengthens trust and moral legitimacy but also expands the function of accounting as a means of building social harmony. This study confirms that Islamic principles have the potential to harmonize modern governance mechanisms with spiritual ethics, while providing a foundation for the development of religious non-profit accountability practices that are locally relevant and adaptable to global demands.